Glutaric aciduria type 1: Diagnosis, clinical features and long‐term outcome in a large cohort of 34 Irish patients. Issue 4 (14th June 2022) - Healy, Lydia; O'Shea, Meabh; McNulty, Jennifer; King, Graham; Twomey, Eilish; Treacy, Eileen; Crushell, Ellen; Hughes, Joanne; Knerr, Ina; Monavari, Ahmad Ardeshir
Abstract: Glutaric aciduria type 1 (GA1) is a rare neurometabolic disorder that can lead to encephalopathic crises and severe dystonic movement disorders. Adherence to strict dietary restriction, in particular a diet low in lysine, carnitine supplementation and emergency treatment in pre‐symptomatic patients diagnosed by high‐risk screen (HRS) or newborn screen (NBS) leads to a favourable outcome. We present biochemical and clinical characteristics and long‐term outcome data of 34 Irish patients with GA1 aged 1–40 years. Sixteen patients were diagnosed clinically, and 17 patients by HRS, prior to introduction of NBS for GA1 in the Republic of Ireland in 2018. One patient was diagnosed by NBS. Clinical diagnosis was at a median of 1 year (range 1 month to 8 years) and by HRS was at a median of 4 days (range 3 days to 11 years). 14/18 (77.8%) diagnosed by HRS or NBS had neither clinical manifestations nor radiological features of GA1, or had radiological features only, compared to 0/16 (0%) diagnosed clinically ( p < 0.001). Patients diagnosed clinically who survived to school‐age were more likely to have significant cerebral palsy and dystonia (7/11; 63.6% vs. 0/13; 0%, p < 0.001). They were less likely to be in mainstream school versus the HRS group (5/10; 50% vs. 12/13; 92.3%; p = 0.012). Clinical events occurring after 6 years of age were unusual, but included spastic diplegia, thalamic haemorrhage, Chiari malformation, pituitary hormone deficiency and epilepsy. The exact aetiology of these events is unclear.